Intraspecific Variation in Thermal Performance Suggests the Presence of Range‐Edge Divergence and Phenotypic Compensation of Northern Individuals in an Introduced Species - Giuseppe Garlaschè; David Drolet; Cyrena Riley; Daniel Small; Kimberly L. Howland; Christopher W. McKindsey; Piero Calosi (Global Ecology and Biogeography, 2025)
Aim Intraspecific variation in functional traits may indicate adaptation to environmental gradients and is crucial to understanding species distributions and range dynamics. We tested the hypotheses that: (1) thermal performance of Littorina littorea follows a countergradient cline, reflecting compensation in northern individuals and (2) local differentiation occurs at the range limits of its non‐native Atlantic distribution. Location Atlantic coast of North America, 46 to 51°N. Time Period 2022. Major Taxa Studied Intertidal gastropods (Littorinidae). Methods Snails from 10 locations, spanning 10° of latitude and approximately 1700 km, were exposed to a gradient of 12 temperatures in the laboratory, and survival, growth, feeding, metabolic rate and heat tolerance were measured. Thermal performance curves obtained were compared and used to calculate performance parameters: that is, thermal optimum, maximum performance and thermal breadth. Results Snails from the northern and southern range edges exhibited a gradual divergence in growth performance parameters relative to central populations. Snails from colder northern locations exhibited greater survival, feeding rate and heat tolerance when exposed to higher temperatures. Main Conclusions The divergent local variation in the growth of individuals from range edges may reflect a stronger selective pressure occurring at the species range limits. In contrast, the clinal countergradient patterns observed for survival, feeding rate and heat tolerance suggest that individuals from northern locations have a greater acclimation capacity to compensate for stronger environmental fluctuations associated with higher latitudes. Our findings suggest that the greater acclimation capacity of northern populations could give them an advantage with the progression of climate changes, supporting the likelihood of a poleward range shift. By revealing trait‐specific trends of variation, our study demonstrates the importance of investigating multiple traits along a wide range of acclimation temperatures in individuals from locations across broad latitudinal gradients to uncover patterns of phenotypic change that would otherwise remain unexplored.

Effect of Aquaculture-Related Diets on the Long-Term Performance and Condition of the Rock Crab, Cancer irroratus - David Drolet; Cyrena Riley; Sonia Robert; Rafael Estrada; Bruno L. Gianasi; Christopher W. McKindsey (Frontiers in Marine Science, 2022)
Shellfish and salmonid aquaculture operations in Eastern Canada attract several mobile epibenthic species as a result of added structural complexity and increased food availability (bivalve fall-off and waste salmonid feed). It is not clear whether the aggregation of predators and scavengers below coastal farms contributes positively or negatively to their population dynamics, due to concerns about the quality of food items found under farms. We conducted an 18-month laboratory study to investigate the effect of diets composed of 1) mixed items, 2) mussels ( Mytilus edulis ), and 3) salmonid feed on the performance and condition of the rock crab, Cancer irroratus . Diet had no impact on crab survival but several negative consequences were observed in crabs fed the salmonid feed diet when compared to the mixed diet: reduced 1) moulting rates during the second growing season, 2) inter-molt growth, 3) gonad and hepatopancreas indices, 4) hemolymph dissolved compounds, 5) hepatopancreatic glycogen, and 6) shell hardness. Crabs fed the mussel diet had similar performance and condition when compared to the mixed diet. Fatty acid composition of muscle, gonad, and hepatopancreas tissues revealed that a salmonid feed diet decreased n3/n6 ratio when compared to a mixed or a mussel diet; those differences were mostly due to increases in the proportions of terrestrial (18:1n9 and 18:2n6) and decreases in proportions of marine essential (20:5n3 and 22:6n3) fatty acids. Together, these results point to a minimal impact of a mussel-only diet on crabs, whereas the salmonid feed diet resulted in negative impacts on condition. Our experimental results explored the consequences of a ‘worst-case scenario’ in which crabs were forced to feed on a single item for a long period of time; the realized impact in field settings will depend on other factors such as consumption of alternate food items underneath a farm, proportion of time spent in farms, and level of overlap between crab habitat and aquaculture facilities.

Experimental Analysis of Survival and Recovery of Ship Fouling Mussels During Transit Between Marine and Freshwaters - Cyrena Riley; David Drolet; Jesica Goldsmit; Jaclyn M. Hill; Kimberly L. Howland; Marie-France Lavoie; Cynthia H. McKenzie; Nathalie Simard; Christopher W. McKindsey (Frontiers in Marine Science, 2022)
Ships and boats may transport whole communities of non-indigenous species (NIS) through hull biofouling, some members of which may become invasive. Several studies have evaluated the diversity of these communities, but very few have analyzed the survival of organisms after their voyages into different and potentially inhospitable conditions. This factor is important to consider because the last port of call approach for risk assessments assumes that if the conditions observed in the last port of call are different from those observed in a receiving port, risks are diminished or null. Using an innovative experimental system, we tested the survival and recovery of the marine blue mussel ( Mytilus edulis ) and the freshwater zebra mussel ( Dreissena polymorpha ) by exposing them to adverse salinity conditions at varying temperatures to simulate ships and boats transiting to ports or marinas with contrasting environmental conditions. Both mussel species, which are well-known for their adaptability to new environments as aquatic NIS, survived better at colder temperatures, with blue mussels surviving up to 14 days in freshwater, and zebra mussels up to 8 days in marine water. This highlights the importance of considering the resistance of fouling organisms to adverse conditions in vector and species risk assessments.